2021
DOI: 10.1021/acs.inorgchem.1c02575
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionation of the Uranyl(V) Coordination Complexes in Aqueous Solution through Outer-Sphere Electron Transfer

Abstract: Among the linear actinyl­(VI/V) cations, the uranyl­(V) species are particularly intriguing because they are unstable and exhibit a unique behavior to undergo H+ promoted disproportionation in aqueous solution and form stable uranyl­(VI) and U­(IV) complexes. This study uses density functional theory (DFT) combined with the conductor-like polarizable continuum model approach to investigate [UO2]2+/+ to [UIVO2] reduction free energies (RFEs) and explores the stability of uranyl­(V) complexes in aqueous solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“… 32 Adsorption studies could not be performed in alkaline conditions because the precipitation of polyanionic species and hydroxides formed under these conditions adversely affects adsorption. 33 Since the natural pH of uranyl is in the range of 4–5, it has been observed that this adsorption pH can be also used for this new material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 32 Adsorption studies could not be performed in alkaline conditions because the precipitation of polyanionic species and hydroxides formed under these conditions adversely affects adsorption. 33 Since the natural pH of uranyl is in the range of 4–5, it has been observed that this adsorption pH can be also used for this new material.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, with an increasing pH, the substitution of polycationic species instead of the dominant UO 2 2+ cation at a low pH leads to increased adsorption . Adsorption studies could not be performed in alkaline conditions because the precipitation of polyanionic species and hydroxides formed under these conditions adversely affects adsorption . Since the natural pH of uranyl is in the range of 4–5, it has been observed that this adsorption pH can be also used for this new material.…”
Section: Resultsmentioning
confidence: 99%
“…However, when the pH is increased, the pentaaquo complex undergoes a hydrolysis reaction and the successive removal of protons from the pentaaquo actinyl complex takes place. For the actinyl species in aqueous solution, to some extent, a mixture of several hydrolyzed species coexists within a pH range of 4–7. In order to mimic neutral to basic conditions, we investigate the adsorption of neutral actinyl aqua complexes onto a semiconducting pyrite surface as an inner-sphere complex with bridging hydroxyl (−OH) groups. A geometry optimization of the neutral uranyl complex results in an extended water structure and formation of hydrogen bonds with one of the uranyl-bound (Figure ) hydroxyl groups and a water molecule.…”
Section: Resultsmentioning
confidence: 99%
“…For the bidentate actinyl adsorption, the calculated PCET energetics suggests that the PCET reaction becomes thermodynamically more favorable on moving across the actinyl series. The neutral actinyl aqua complexes correspond to higher pH conditions (pH 4–6), and at high pH, hydrolysis becomes more probable and equilibrium between various hydrolyzed species is anticipated. We use neutral actinyl­(VI) aqua complexes as models for surface reductions by PCET pathways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation